Process-Oriented Inquiry Learning Enhances StudentsÃ¢â¬â¢ Critical Thinking Skills - Nurussaniah Nurussaniah; Ira Nofita Sari (Jurnal Pijar Mipa, 2019)
The objective of this study is to determine the applied inquiry learning to improve the studentsÃ¢â¬â¢ critical thinking skills. This study uses non-equivalent control group design. Students in this study were divided into two class activities. The experimental class was treated with the application of inquiry learning, whereas the control class was given the conventional learning. In this study, the studentsÃ¢â¬â¢ critical thinking skill is obtained through a test. The test used was a critical thinking skill test consisting of five questions with the following indicators, namely: completing information, finding and defining problems, recognizing assumptions and formulating hypothesis. The result shows that the gain value in the experimental class is higher than the gain value in the control class. It indicates that the improvement of studentsÃ¢â¬â¢ critical thinking skills in the experimental class is higher than the studentsÃ¢â¬â¢ critical thinking skills in the control class. Therefore, it can be said that the application of inquiry learning provides a more significant improvement than conventional learning. The studentsÃ¢â¬â¢ critical thinking skills show an increase at the medium category on the aspect of completing information, recognizing assumption and formulating hypothesis. Meanwhile, on aspect of finding and defining problem, studentsÃ¢â¬â¢ critical thinking skills show an increase at the low category or it can also be said it does not show any increase.